2008
DOI: 10.1590/s0102-76382008000300014
|View full text |Cite
|
Sign up to set email alerts
|

Substituição valvar mitral com papilopexia cruzada e constrição anular em pacientes com insuficiência cardíaca

Abstract: Substituição valvar mitral com papilopexia cruzada e constrição anular em pacientes com insuficiência cardíacaMitral valve replacement with crossed papillopexy and annular constriction in heart failure patients Abstract Objective: To analyze the short-term and mid-term followups of patients with heart failure and moderate to severe mitral valve insufficiency and who have undergone mitral valve replacement with crossed papillopexy and annular constriction.Methods: Thirteen patients in NYHA functional class III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In Brazil, it is important to emphasize the studies by Gomes et al [63] and Benfatti et al [64] about the benefits of MV replacement using the technique of cross papiloplexia in patients with heart failure and moderate/ severe MI ( Figure 6). In these studies, the group found that this technique was able to promote a significant left ventricular functional improvement as well as favorable ventricular and atrial remodeling.…”
Section: The Importance Of Preservation Of the Subvalvular Apparatus mentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, it is important to emphasize the studies by Gomes et al [63] and Benfatti et al [64] about the benefits of MV replacement using the technique of cross papiloplexia in patients with heart failure and moderate/ severe MI ( Figure 6). In these studies, the group found that this technique was able to promote a significant left ventricular functional improvement as well as favorable ventricular and atrial remodeling.…”
Section: The Importance Of Preservation Of the Subvalvular Apparatus mentioning
confidence: 99%
“…It is also important to highlight the original idea of Gomes et al [63], in Belo Horizonte, of association of crossed papillopexy to valve replacement in patients with DC and FMI, and have been useful in reversing at least partially, the dilation of the left atrium and ventricle, with significant functional recovery of the latter [64].…”
Section: Brazilian Contribution In the Correction Of The Functional Mmentioning
confidence: 99%
“…Entering the heart chambers was made possible by this discovery in an almost bloodless field and to correct birth [7][8][9][10] or acquired defects [11][12][13][14][15], which restricted the lives of those who had the misfortune to present problems in the blood propulsive organ and in their own lives.…”
mentioning
confidence: 99%